Shipwrecks, Legal Landscapes and Mediterranean Paradigms Gone Under Sea - Mataix Ferrándiz, Emilia (Brill, 2022)
This book changes our understanding of the Roman conceptions about the sea by placing the focus on shipwrecks as events that act as bridges between the sea and the land. The study explores the different Roman legal definitions of these spaces, and how individuals of divergent legal statuses interacted within these areas. Its main purpose is to chart and analyse the Roman conception of the maritime landscape from the Late Republican until the Severan period. This book integrates maritime history and ethnography with the physical remains of past maritime systems, such as shipwrecks, ports, villages, fortifications, and documented legal rulings.